2017
DOI: 10.1177/0194599817695800
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in 807 Patients with Vestibular Schwannoma: Comparing Treatment Modalities

Abstract: Objective In vestibular schwannoma treatment, the choice among treatment modalities is controversial. The first aim of this study was to examine the quality of life of patients with vestibular schwannoma having undergone observation, radiation therapy, or microsurgical resection. The second aim was to examine the relationship between perceived symptoms and quality of life. Last, the association between quality of life and time since treatment was studied. Study Design Cross-sectional study. Setting Tertiary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 41 publications
9
73
0
3
Order By: Relevance
“…Three studies showed that MS patients had worse QOL than those in the other groups . Soulier et al reported better QOL in patients with small tumours (<10 mm) undergoing observation because there was no active treatment, so patients did not feel sick. Betchen et al showed that postoperative hearing, facial functioning and time since MS had no significant impact on QOL as assessed by the SF‐36.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies showed that MS patients had worse QOL than those in the other groups . Soulier et al reported better QOL in patients with small tumours (<10 mm) undergoing observation because there was no active treatment, so patients did not feel sick. Betchen et al showed that postoperative hearing, facial functioning and time since MS had no significant impact on QOL as assessed by the SF‐36.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with smaller VSs report a higher overall quality of life when managed with observation compared to surgical intervention, even when controlling for hearing preservation microsurgical approaches . Among patients undergoing treatment, those with smaller tumors approached with either surgery or stereotactic radiation have higher rates of hearing preservation and higher overall quality of life than those with larger tumors .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 34 studies (n = 5,560) met the selection criteria and were included in the analysis (Fig. , Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Five studies compared three interventions (MS, RT, and OB). MS and RT were compared in five studies, whereas MS and OB were compared in one .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation